TRATAMENTO DE SEMENTES DE MILHO COM FUNGICIDAS E INDUTOR DE RESISTÊNCIA E PULVERIZAÇÃO FOLIAR PARA O CONTROLE DA FERRUGEM COMUM DO MILHO (Puccinia sorghi Schw.) - Schipanski, Carlos André (2011)
The aim of this study was to evaluate the effects of fungicides and resistance inducer acibenzolar-S-methyl applied as seed treatment associated with foliar applications sprays of fungicides in corn on the control of common rust of corn, caused by the fungus Puccinia sorghi. To achieve this objective to experiments were carried out. On the first experiment, the P. sorghi was inoculated in the laboratory and the effects of the following fungicides were evaluated: fluquinconazol (10 g ia/60.000 seed 1), flutriafol (3 g ai), azoxystrobin (15 g ia), carbendazin ( 10 g ia), carbendazin + thiram (9 + 21 g ia), carboxin + thiram (12 + 12 g ia), fludioxonil + metalaxyl - m (3 + 7.5 g ia) fludioxonil + mefenoxam + thiabendazole (1 + 6 +0.8 g ia), difenoconazole (6 g ia), acibenzolar-s-methyl (12.5 g ia) and thiophanate methyl +fluazinam (14 + 2.1 g ia). After inoculation, the plants were assessed to count the number of lesions at 7, 14 and 21 days after inoculation (DAI), fresh and dry weight, root length and shoot at 21 DAI. After the assessments it was observed that the fungicides azoxystrobin and fluquinconazol had the highest levels of control of the disease, and the levels of control from the other products tested varied from 23.7 to 49.9% control. No effects of these products were observed on the green and dry weight, length of roots and shoots of maize plants. In the second experiment conducted under field conditions, the effects of the following fungicides were evaluated: fluquinconazol (10 g ia/60.000 seed-1), azoxystrobin (15 g ia) carbendazin (10 g ia) in seed treatment in combination with foliar fungicides sprays. At the V4 stage, the fungicides azoxystrobin (60 g ai ha-1) and azoxystrobin + cyproconazole (60 +24 g ai ha-1) were used and at the V9 stage azoxystrobin + cyproconazole (70 + 28 g ai ha-1). The treatments were combined in a 4x3x2 factorial structure, with 24 treatments and four replications. The rust severity assessments levels started after sowing and the plumule leaf emergence, considering as 1 (full emergence of the plumule leaf above ground), 7, 14, 21, 28, 35 , 42, 49, 56 days after emergence (DAE), severity of common rust at the stages VT, R3 and R5, plant height at 21 and 28 DAE, incidence of stalk rot and mold grains, the 1000 grain weight, final stand and productivity. A significant effect of the fungicides azoxystrobin, fluquinconazol and carbendazin as seed treatment on reducing the severity of common rust of corn until 56 DAE. The treatment with azoxystrobin presented a better result. However, the effect of the seed treatment was suppressed at the 28 DAE when associated with the foliar sprays. The foliar sprays in V4 stage reduced the severity of the common rust and no differences between the fungicides azoxystrobin and azoxystrobin + cyproconazole were oberved. The spray with azoxystrobin + cyproconazole in V9 stage also contributed to the decrease of the disease severity. A greater reduction of disease severity was observed when the sprays were done at the V4 and V9 stages. No treatment effect was observed on the incidence of stalk rot, grain molds, final stand, southern rust and gray leaf spot severity. Only the carbendazin fungicide seed treatment presented a significant effect in relation to the yield.